Do smokers have greater risk of delayed and non-union after fracture, osteotomy and arthrodesis?: a systematic review with meta-analysis - Pearson, Richard G.; Clement, R.G.E.; Edwards, K.L.; Scammell, Brigitte E. (BMJ Publishing Group, 2016)
Objectives: Systematic review and meta-analysis of published observational cohort studies. To quantify the increased risk smokers have of experiencing a delayed and/or non-union in fractures, spinal fusion, osteotomy, arthrodesis or established non-unions.